Fehlbildungen an Hand und Unterarm: postpartal auffallend = Malformations of hand and forearm - Unglaub, Frank (Der Orthopäde, 2016)
Many congenital malformations of the hand and forearm, e. g. polydactyly, thumb duplication, syndactyly and radial aplasia, are already evident at birth and newborns are promptly referred to specialized departments. In contrast, orthopedic surgeons are often confronted with malformations of the hand and forearm, which gradually become clinically conspicuous during growth. This review article focuses on these specific malformations, which regularly upset the patients in practice and in most cases the parents even more so. In addition to the diagnostics and differential diagnostics, the conservative and surgical treatment options are presented.